Respon Fisiologis dan Produksi Pucuk Kolesom (Talinum Triangulare (Jacq.) Willd) Terhadap Aplikasi Pupuk Nitrogen+Kalium Melalui Tanah dan Daun - Hilda Susanti; Slamet Susanto; Sandra Arifin Azis; Maya Melati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2014)
The experiment was conducted in Leuwikopo, Dramaga, Bogor, Indonesia to study the effect of soil and foliar applications of nitrogen+potassium fertilizer on waterleaf shoot (Talinum triangulare (Jacq.) Willd) physiological aspect and production. A randomized complete block design was used with 3 replications and 4 treatments. The treatments were different rates of N+K for soil application with or without foliar application, they were 100% N+K rates of soil application (150 kg urea + 150 kg KCl/ha); 100, 75, and 50% N+K rates of soil application added with foliar application of 0.2% urea and 0.1% KCl. Fertilizers were applied on soil on 0, 30, and 60 days after planting, while foliar applications were conducted on 15, 30, 45, and 60 days after planting. The result showed that the highest production of waterleaf shoot were produced by 100% soil application of N+K at 75 days after planting (117.04 g/plant); chlorophyll and sugar content was not influenced by all the treatments in vegetative fase.